Reseña de Croft, William y Cruse, Alan (2004). Cognitive Linguistics, Cambridge: Cambridge University Press. - José Luis Berbeira Gardón (Pragmalingüística)
Se trata de una reseña sobre Croft, William y Cruse, Alan (2004). Cognitive Linguistics, Cambridge: Cambridge University Press. ISBN 0 521 66770. 356 págs.